Ruang Kebersamaan: Suatu Kajian Sinergitas Dan Kreativitas Di Ruang Publik Kota - Heryanto, Bambang; Jamila, Rona Fika; Dharmaraty, Ashri Prawesthi (Jurnal Pembangunan Wilayah dan Kota, 2020)
The purpose of this research is to examine public space services in meeting the needs and activities of the community in their spare time. Synergy and creativity are two factors to measure how the public space functions and functions properly. A good public space has an index of synergy and creativity that can be used collectively and is interesting for its visitors to interact with. The synergy of public spaces is manifested in how compatible spaces are mutually compatible in serving the activities of its users. Creativity is how existing facilities have an attractive form so that visitors can use them together. The method used in this study is to spread questions to visitors who visit heritage areas in the old city area in Jakarta. Descriptive description is used in research to determine the togetherness aspect of the community using public space in carrying out the needs and activities of visitors. The results of this study found that most visitors like to do activities together, share space with other visitors, especially if there are events such as music, culture or carnivals, but most are still embarrassed to initiate the initiative to invite other visitors, besides that in Kota Tua the visitors also sometimes want a little privacy, so additional furniture such as seating and shade is needed.